2018
DOI: 10.1155/2018/1781036
|View full text |Cite
|
Sign up to set email alerts
|

Absorption ofCodonopsis pilosulaSaponins by Coexisting Polysaccharides Alleviates Gut Microbial Dysbiosis with Dextran Sulfate Sodium-Induced Colitis in Model Mice

Abstract: Objectives Inflammatory Bowel Disease (IBD) is an autoimmune disease, and the gut microbiota has become a new therapeutic target. Herbal medicine (HM) has shown good efficacy in the clinical treatment of IBD; however, the synergistic actions of the dominant chemicals in HM decoctions are unclear. Methods In this study, we explored whether the complicated interconnections between HM and the gut microbiota could allow crosstalk between HM ingredients. Saponins and polysaccharides, i.e., the dominant chemicals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 81 publications
3
41
2
Order By: Relevance
“…The regulation of the intestinal microbiome has become an effective therapeutic tool against age-related chronic diseases (53). certain studies have indicated that Codonopsis pilosula polysaccharide, one of the main components of Codonopsis pilosula, can be used as a prebiotic to regulate intestinal microbiota (54,55). The findings of the present study support this point; the specific underlying mechanism warrant further investigation in future studies.…”
Section: Discussionsupporting
confidence: 79%
“…The regulation of the intestinal microbiome has become an effective therapeutic tool against age-related chronic diseases (53). certain studies have indicated that Codonopsis pilosula polysaccharide, one of the main components of Codonopsis pilosula, can be used as a prebiotic to regulate intestinal microbiota (54,55). The findings of the present study support this point; the specific underlying mechanism warrant further investigation in future studies.…”
Section: Discussionsupporting
confidence: 79%
“…The CHF was authenticated and standardized based on marker compounds according to the Chinese Pharmacopoeia 2005 [37]. Jing Yp indicated that Codonopsis pilosula polysaccharides have good prebiotic properties by inhibiting the growth of Desulfovibrio , Alistipes , and Helicobacter and stimulating the growth of Bifidobacterium , Lactobacillus , and Akkermansia [38]. Wang JH showed that R. Atractylodis significantly enhances the abundance of Bifidobacterium and Akkermansia and the Bacteroidetes/Firmicutes ratio [39].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Codonopsis pilosula Nannf polysaccharides could increase three probiotics, namely Bifidobacterium spp., Lactobacillus spp., and Akkermansia spp., and decrease pathogenic bacteria, including Desulfovibrio spp., Alistipes spp., and Helicobacter spp. in mice with colitis [26]. Huangqin decoction increased the amount of Lactobacillus and decreased the abundance of Desulfovibrio and Helicobacter in the treatment of dextran sulfate sodium (DSS)-induced inflammation [27].…”
Section: Introductionmentioning
confidence: 99%